Exploring unsupervised query paraphrasing to identify relevant search phrases for a literature review - Laura-Maria Peltonen; Miretta Tommila; Hans Moen (IOS Press, 2022)
Literature databases have multifaceted search options, but emerging research areas do not have an established terminology and therefore it is difficult to find relevant literature when conducting a review. This study aimed to explore if an unsupervised paraphrasing approach is useful in identifying relevant search phrases for a literature review on an emerging research topic – situational leadership in critical care. Using an initial set of 12 search phrases, the system was used to propose additional phrases, which were manually classified and further used in an expanded PubMed database search. Finally, we assessed the papers found with the expanded search and compared this to the initial search results. As a result, the expanded search more than tripled the search results, from 182 to 673 papers. The expanded search also more than tripled the number of relevant papers, from 12 in the original search to 39 in the expanded search.